Biochemical characterization, cDNA cloning, and molecular modeling of araujiain aII, a papain-like cysteine protease from Araujia angustifolia latex - Obregón, Walter David (2011)
Araujiain aII, the protease with highest specific activity purified from latex of Araujia angustifolia (Apocynaceae), shows optimum proteolytic activity at alkaline pH, and it is completely inhibited by the irreversible inhibitor of cysteine proteases trans-epoxysucciny-l-leucyl-amido(4-guanidino) butane. It exhibits esterolytic activity on several N-α-Cbz-amino acid p-nitrophenyl esters with a preference for Gln, Ala, and Gly derivatives. Kinetic enzymatic assays were performed with the thiol proteinase substrate p-Glu-Phe-Leu-p-nitroanilide (Kₘ = 0.18 ± 0.03 mM, kcat = 1.078 ± 0.055 s⁻¹, kcat/Kₘ = 5.99 ± 0.57 s⁻¹ mM⁻¹). The enzyme has a pI value above 9.3 and a molecular mass of 23.528 kDa determined by mass spectrometry. cDNA of the peptidase was obtained by reverse transcription-PCR starting from total RNA isolated from latex. The deduced amino acid sequence was confirmed by peptide mass fingerprinting analysis. The N-terminus of the mature protein was determined by automated sequencing using Edman’s degradation and compared with the sequence deduced from cDNA. The full araujiain aII sequence was thus obtained with a total of 213 amino acid residues. The peptidase, as well as other Apocynaceae latex peptidases, is a member of the subfamily C1A of cysteine proteases. The enzyme belongs to the alpha + beta class of proteins, with two disulfide bridges (Cys22–Cys63 and Cys56–Cys95) in the alpha domain, and another one (Cys150–Cys201) in the beta domain, as was suggested by molecular modeling.